What constrains Africa's exports? - Caroline Freund; Nadia Rocha (World Trade Organization (WTO), 2010)
We examine the effects of transit, documentation, and ports and customs delays on Africa's exports. We find that transit delays have the most economically and statically significant effect on exports. A one day reduction in inland travel times leads to a 7 percent increase in exports. Put another way, a one day reduction in inland travel times translates into 1.5 percentage point decrease in all importing-country tariffs. In contrast, longer delays in the other areas have a far smaller impact on trade. We control for the possibility that greater trade leads to shorter delays in three ways. First, we examine the effect of trade times on exports of new products. Second, we evaluate the effect of delays in a transit country on the exports of landlocked countries. Third, we examine whether delays affect time-sensitive goods relatively more. We show that large transit delays are relatively more harmful because of high within-country variation.
Keywords: F13; F14; O55; 330; trade facilitation; export times; transit delays; gravity models; Export; Außenhandelsförderung; Verkehrsinfrastruktur; Afrika